Pengaruh Komunikasi Pemasaran dan Citra Destinasi Terhadap Kunjungan Ulang Ke Atlantis Land Surabaya - Nabilla Ainun Nadhiyyah; Ersa Dina Fitaloka; Mila Hariani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of marketing communications and destination image on repeat visits to Atlantis Land Surabaya. The research population consisted of people who had visited Atlantis Land, with a sample of 100 respondents selected using purposive sampling techniques. Data collection was carried out using a questionnaire distributed via Google Form. The results of the analysis show that the two independent variables, namely marketing communication and destination image, have a significant influence on repeat visits. This research provides insight for Atlantis Land managers to understand visitors and design marketing strategies that suit their needs.